Electric-Field Control of Magnetoresistance Behavior in a Conetic Alloy Thin Film/Pb(Mg1/3Nb2/3)0.7Ti0.3O3 Multiferroic Heterostructure - Wang, Cangmin; Huang, Wenyu; Wang, Chi; Li, Lu; Wei, Chong; Sun, Yuchen; Ge, Weifeng; Mao, Xiaoli; Li, Qiang; Yang, Yuanjun; Jia, Cheng; Zhang, Hui; et al. (Frontiers in Materials, 2022)
In this work, we investigate the influence of electric fields (E-fields) on the room-temperature magnetotransport behavior of an artificial multiferroic heterostructure, a Conetic alloy (Ni77Fe14Cu5Mo4) thin film/Pb(Mg1/3Nb2/3)0.7Ti0.3O3 (011). When the external magnetic field is parallel to the applied current, the switching field increases from 0.8 to 3.3 Oe at 0 and 8 kV/cm, respectively, and the corresponding magnetoresistance (MR) ratio at 20 Oe respectively decreases from 0.14% to 0.03% at 0 and 8 kV/cm. However, when the external magnetic field is perpendicular to the current, the switching field decreases from 10.1 to 1.7 Oe at 0 and 8 kV/cm, and the MR ratio in such a case decreases from −0.001% to −0.10%, respectively. Consequently, under the parallel and perpendicular modes, the tunabilities of the switching field are approximately +313% and −83%, and the MR ratio tunabilities under E-fields are approximately −79% and +9900%, respectively. Such a large and anisotropic tunability of both the switching field and MR ratio is attributed to the ultrasoft magnetic property of the Conetic alloy thin film and anisotropic in-plane strain-mediated magnetoelectric coupling. However, the anisotropic MR ratio is approximately 0.15% and does not vary with the applied E-fields owing to the intrinsic property of Conetic thin films using transfer and circle transfer curve measurements, rather than the magnetization rotation caused by E-field-induced magnetoelastic anisotropy. This work demonstrates that multiferroic heterostructures with electrically tunable MR show considerable potential in designing energy-efficient electronic and spintronic devices.